Design of Batch Reactor for the Production of SnCl2 Particles - Yohanes Ivan Benaya Parlindungan Nainggolan; Risti Ragaditha; Asep Bayu Dani Nandiyanto (Penerbit Goodwood, 2025)
Purpose: This study aims to design and evaluate a batch reactor for industrial-scale production of Stannous Chloride (SnCl2) from Indonesian tin resources, supporting downstream processing of tin into higher-value chemical products.Methodology: A computational design approach was applied using sequential chemical engineering equations in Microsoft Excel. The process is based on the reaction between Tin (Sn) and Hydrochloric Acid (HCl). The reactor is designed as a cylindrical batch vessel with a dished top and conical bottom, made of stainless-steel SA 240 Grade 316. Operating conditions include 80°C, 1 atm, and 1-hour batch time, with 1,000 kg/h tin feed and 95% conversion. Mass balance, sizing, and mechanical design calculations were performed, including stirrer specifications. Results: The reactor has a volume of 29.0184 ft³, diameter of 2.7889 ft, and height of 5.6690 ft. Mass balance yields 1,517.31 kg/h SnCl? and 16.13 kg/h H?. The system uses a 2 Hp axial turbine stirrer with 16.7334 in impeller diameter.Conclusions: The designed reactor demonstrates technical feasibility for industrial SnCl? production and complies with ASME pressure vessel standards.Limitations: The model does not include effectiveness factors for diffusion limitations in heterogeneous reactions. Contributions: This study provides a validated engineering design reference for SnCl? production and supports downstream tin industry development in Indonesia